ERP: framework based implementation - a case study - Mohammed Hussain, K; Venkata Subramanian, D; Thangakumar, J; Pradeep Kumar, K (International Journal of Engineering and Technology, 2018)
ERP implementation projects are some of the most critical and complex project implementations. Most of the fortune organizations and institutions will adopt the large scale ERP to standardize their business needs and upgrade their IT systems on par with the current technologies. ERP is one of the solutions for managing Enterprises; Most of the ERPs are suitable for Manufacturing and IT industries. This research paper discusses the framework which helps to minimize the implementation of data conversion processes. Most of the organizations use the migration manually and involve a significant duration of time of many functional users; thus the work proposes the creation of data model templates and Smart Data Load Accelerator. The proposed work also helps to reduce the development time.